Perbankan Syariah Di Bangladesh - Salwa Latipah; Zulfahri Salim; Khaidar rahmaini jamila (CV. ITTC INDONESIA, 2025)
Bangladesh, home to one of the world's largest Muslim populations, holds enormous potential for the development of Islamic banking. More than 90% of Bangladesh's population is Muslim, fueling a growing need and demand for financial services based on Islamic principles. Islamic banking is viewed as an alternative financial system that not only aligns with Islamic values ​​but also promotes justice, transparency, and public welfare. This study aims to examine the development, potential, and role of Islamic banking in Bangladesh in supporting the national financial system. The research method used is literature review with a qualitative descriptive approach. Data were obtained through the collection of various written sources, such as books, scientific journals, financial institution reports, and official publications relevant to the topic of Islamic banking in Bangladesh. The collected data were then systematically analyzed to obtain a comprehensive picture of the condition and prospects of Islamic banking in the country. The study results indicate that Islamic banking in Bangladesh has experienced significant development along with increasing public awareness of the Islamic financial system. However, several challenges remain, such as limited regulations, Islamic financial literacy, and competition with conventional banking. Therefore, policy support and institutional strengthening are needed to optimize the role of Islamic banking in the Bangladeshi economy.